Building Agents with OpenAI Agents SDK : Create Practical AI Agents and Agentic Systems Through Hands-On Projects. - Habib, Henry; ProQuest (firma) (Birmingham : Packt Publishing, Limited, 2025)
Master OpenAI's Agents SDK to design production-ready AI agents and agentic systems that solve real-world problems with practical guidanceGet your book with a free PDF, AI Assistant, and Next-Gen Reader Key Features Gain a complete understanding of the OpenAI Agents SDK features including models, tools, memory, guardrails, orchestration, tracing.
End-to-end testing -- Unit testing -- Summary -- Part 3: Build AI Agents -- Chapter 9: Building AI Agents and Agentic Systems -- Technical requirements -- Building a customer service employee AI agent -- Setting up the database -- Setting up a vector store -- Creating a function tool to query data -- Creating a vector store search tool -- Creating an input guardrail -- Creating a retention agent -- Creating a customer service agent -- Building the runner -- Testing the agent -- Orchestrating an automated multi-agent workflow -- Setting up a customer database -- Setting up the transcripts JSON -- Creating function tools to retrieve data and search the web -- Creating the customer research agent -- Creating the email creation agent -- Orchestrating the workflow -- Testing the workflow -- Summary -- Packt Page -- Other Books You May Enjoy -- Index -- Blank Page.
Description based on publisher supplied metadata and other sources.
Electronic reproduction. Ann Arbor, Michigan : ProQuest Ebook Central, 2026. Available via World Wide Web. Access may be limited to ProQuest Ebook Central affiliated libraries.
Keywords: elektronické knihy; electronic books